Peluang berwirausaha sebagai librarypreneur di era teknologi informasi - Siti Rohaya; F. Trisakti Haryadi; Alia Bihrajihant Raya (Perpustakaan Universitas Gadjah Mada, 2023)
Introduction. This study examines the business opportunities in the field of library and Information run by graduates of the Library Science program at UIN Sunan Kalijaga and UIN Syarif Hidayatullah. Research methods. This research is a qualitative research with a case study approach. Data obtained through observation, interviews, and documentation. Determination of informants through snowball sampling while the analysis was carried out descriptively. Results and Discussion. The development of Information Technology presents a wide range of business opportunities in the field of library and information. Entrepreneurship is a promising option for Library Science graduates. These efforts include library management, library automation; utilization of digital Technology; Information System Design; information consulting; training and teaching; software and hardware development; procurement of library facilities and infrastructure. The focus of this research is librarypreneurship and librarypreneur. Conclusions. The emergence of librarypreneurs is an effect of the creativity and innovation of library science graduates in capturing existing opportunities.